ChemInform Abstract: Ca4Au10Zn3 — A Substitution Variant of AlB2 by Incorporation of Zn3 Triangles. Issue 49 (December 2015) - Gerke, Birgit; Hoffmann, Rolf‐Dieter; Poettgen, Rainer
Abstract: Single crystals of the title compound are selected from high‐frequency melts of the elements in stoichiometric ratio with a 5 at.% Zn excess (sealed Ta ampoules, 925 K, 3 h).